Key performance measures for colonoscopy in the Polish Colonoscopy Screening Program - Bugajski, Marek; Rupinski, Maciej; Wieszczy, Paulina; Pisera, Małgorzata; Regula, Jaroslaw; Kaminski, Michal F. (Endoscopy, 2019)
Background The European Society of Gastrointestinal Endoscopy (ESGE) has published guidelines on key performance measures for colonoscopy. We analyzed whether those standards were met in the Polish Colonoscopy Screening Program (PCSP) and whether the monitoring was feasible.Methods We analyzed database records for 43 277 PCSP participants (25 PCSP centers) for the years 2014 – 2015. We used the guideline definitions to calculate values for all key performance measures and compared these with the proposed standards at individual, center, and program level. All data were acquired from the PCSP database, apart from complication data which was assessed from external registries.Results At the program level, four of five minimum standards and one of two target standards (no set minimum standard) were met. Adequate bowel preparation rate was 91.3 % for the whole program (range among individual centers 79.2 % – 99.2 %). Cecal intubation rate was 97.4 % (93.4 % – 99.4 %). Adenoma detection rate was 29.8 % (19.1 % – 39.1 %). An appropriate polypectomy technique was applied in 62.7 % of cases (0.4 % – 97.8 %). Regarding complications, 7-day hospitalization rate after screening colonoscopy was 0.3 % (n = 127), and 30-day all-cause mortality was 0.02 % (n = 9). Patient feedback was assessed in 66.2 % of colonoscopies (7.6 % – 81.8 %). Appropriate post-polypectomy surveillance was proposed in 95.4 % of cases (range 84.9 % – -99.7 %). It was easy to monitor 6 of 7 key performance measures within the PCSP database, but monitoring complications required the additional effort of data extraction from external registries.Conclusions The PCSP meets most proposed minimum standards at program level. Some centers need additional interventions to meet the complete set of quality standards. Use of ESGE performance measures for monitoring colonoscopy is generally feasible in the setting of the colonoscopy screening program.